Molecular phylogeny and morphologıcal evaluatıon of the relıct-endemıc epıgaea gaultherıoıdes (Boıss. & Balansa) takht (Bangladesh Journal of Botany, 2026)
The genus Epigaea L., belonging to Ericaceae is represented worldwide by 3 species, viz.,  E. repens L., E. asiatica Maxim. and E. gaultherioides (Boiss. & Balansa) Takht.,  exhibit limited distribution. Comprehensive study on phylogenetic differences of the relict E. gaultherioides is lacking and the phylogenetic relatedness of this species to two other species of Epigaea L. of the family has not yet been determined. In this study, the morphological and molecular differences of the Epigaea species and taxonomic description of relict E. gaultherioides were given in detail. nrDNA (ITS 4-5) and plastid (matK, rbcL) sequences were used for phylogenetic analysis. Morphologically, the main differences between E. gaultherioides and the other two species are in the color, shape, and size of corolla. Molecular results from ML analyses indicated that Epigaea L. is monophyletic and clearly separated from other genera within the Ericaceae in the phylogenetic trees and also E. gaultherioides is phylogenetically distinct from the other two species.Bangladesh J. Bot. 55(2): 229-237, 2026 (June)